Touaregs 2.0 - Pierre Peraldi-Mittelette (Netcom)
Ethnography of communication of the Tuareg in Europe allows to conceive a global process of communication in which the use of internet takes an essential place. The rhetoric of these networks in Diaspora approaches punctually aspects of the culture by proposing a pointillist portrait of the Tuareg by means of internet in particular social networks. The interest studying Tuareg diaspora by the prism of Internet is to understand the declarative digital identity proposed by Tuaregs on the Internet.